Management and phenotypic characterization of donkeys of Rajasthan - PAL, YASH; LEGHA, R A; LAL, NIRANJAN; BHARDWAJ, ANURADHA; CHAUHAN, MAMTA; KUMAR, SANJAY; SHARMA, R C; GUPTA, A K (The Indian Journal of Animal Sciences, 2013)
The donkey, a very important draught animal of Rajasthan, is mostly used by nomadic pastoralists in brick kilns for carrying bricks and in pneumatic wheel cart for rural and urban transport. The study was conducted to know the socioeconomic role in the life of donkey keepers of the region, housing, feed and fodder, health management of donkeys adopted by them and to phenotypically characterize local donkeys available in different regions of Rajasthan. Small sized light and dark gray donkeys of Rajasthan play important role in providing draught power in pastoral migration and other draught operations. The donkeys are very hardy and surefooted. Zebra marking on legs and dorsal stripes on back could be seen. Donkeys are of many coat colours but light and dark gray is more prevalent, accompanied by shoulder crosses, dark ear markings, white muzzles, eye rings, white bellies and inner legs. In adult donkeys, body length was almost equal to height and width. Mean body length, height at withers, heart girth, knee height and height at hock of adult donkeys were 97.57±0.579, 97.55±0.584, 101.74±0.670, 31.64±0.275, 40.14±0.281, respectively. Hooves of donkeys are small and round with upright pasterns. Donkey owners were offering soya straw, gram straw, groundnut straw, rice straw, moth straw and dhania jiri as dry roughage. Vaccination, insurance and use of disinfectants were not adopted by any of the donkey owner. The donkey works hard for a long time but its role is not appreciated. Donkeys are the major source of livelihood of the donkey keepers studied. Majority of the owners were not aware about the symptoms of estrus jenney and their jennies were getting pregnant through the natural covering during grazing.